The Impact of Life Meaning and Spiritual Well-Being on the Quality of Life in Patients with Chronic Kidney Failure at Purbalingga Hospital - Munjiati, (International Journal of Scientific Research and Management (IJSRM), 2025)
Chronic Kidney Failure (CKD) is a progressive and irreversible condition that necessitates lifelong renal replacement therapies such as hemodialysis or kidney transplantation. Globally, the prevalence of CKD has risen significantly, accompanied by high mortality and morbidity rates. In Indonesia, CKD continues to grow as a public health challenge, with many patients reliant on hemodialysis, which, while improving survival, brings physical, psychological, social, and financial burdens. These challenges often lead to diminished quality of life, emphasizing the need for holistic support systems.This study highlights the critical role of spiritual well-being and the sense of meaning in life in enhancing the quality of life for CKD patients undergoing hemodialysis. Spiritual well-being fosters hope and acceptance, empowering patients to cope with chronic illness while finding meaning amidst adversity. A higher sense of spiritual and existential well-being correlates positively with improved physical, psychological, social, and environmental health domains. By integrating spiritual well-being with the concept of meaning in life, patients can achieve greater resilience and an enhanced quality of life. This therapeutic interplay underscores the need for comprehensive interventions that address not only physical health but also the psychosocial and spiritual dimensions of CKD care.